Internasionalisasi dan Reformasi Perguruan Tinggi: Studi Kasus Pada Lembaga Pendidikan Tinggi Muhammadiyah - Binangkit, Intan Diane; Siregar, Dede Iskandar (Universitas Negeri Surabaya, 2020)
Educational institutions, especially tertiary education, are designed to spearhead the development of the quality of human resources. The strategic role needed by tertiary institutions makes intensive attention to improving its quality. This article discusses how to analyze Muhammadiyah Universities (PTM) to transform institutions from national to international scale. This article is carried out by discussing case studies from PTM. Data collection was carried out through several meetings gathering desk research, interviews, and document studies. Analyzes were performed by pattern matching, cross-case synthesis, and explanation building. The results show several aspects of PTM internationalization. Good governance in achieving the objectives of internationalization must be carried out in the form of a vision, mission, goals, quality policy and strategic plan. An internationalization process that demands specialized institutions that require international cooperation and activities. To support internationalization, the development of HR and decision-making systems that are fast and not rigid are important to consider.